2017
DOI: 10.14238/sp18.3.2016.220-5
|View full text |Cite
|
Sign up to set email alerts
|

Kelainan Kardiovaskular pada Anak dengan Berbagai Stadium Penyakit Ginjal Kronik

Abstract: Latar belakang. Penyakit kardiovaskular (PKV) merupakan penyebab morbiditas dan mortalitas tersering pada penyakit ginjal kronik (PGK) anak. Hipertrofi ventrikel kiri (LVH) dan disfungsi diastolik paling awal terlihat. Tujuan. Mengetahui proporsi PKV pada PGK stadium 1, hubungan stadium PGK dengan LVH, dan disfungsi jantung. ). Uji stastistik bermakna bila p<0,05. Hasil. Rerata umur subjek 9,1(3,8) tahun. LVH pada 1 dari 3 subjek PGK stadium 1 dan 61,5% pada PGK seluruh stadium, terbanyak stadium 5. Tidak terd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Pabuti et al found that 50% of the pediatric CKD subjects in his study were in stage V. The large proportion of advanced stage CKD may have been due to lack of public awareness, such that patients usually consulted a physician late, or lack of competence among healthcare workers in the early detection of CKD in children. 4 Slightly more than half of subjects had failure to thrive (51.2%), indicating that chronic nutritional disorders are common in children with CKD. Failure to thrive in children with CKD may be caused by several factors, including malnutrition, dehydration, hyponatremia, metabolic acidosis, uremia, anemia, renal osteodystrophy, and growth hormone resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pabuti et al found that 50% of the pediatric CKD subjects in his study were in stage V. The large proportion of advanced stage CKD may have been due to lack of public awareness, such that patients usually consulted a physician late, or lack of competence among healthcare workers in the early detection of CKD in children. 4 Slightly more than half of subjects had failure to thrive (51.2%), indicating that chronic nutritional disorders are common in children with CKD. Failure to thrive in children with CKD may be caused by several factors, including malnutrition, dehydration, hyponatremia, metabolic acidosis, uremia, anemia, renal osteodystrophy, and growth hormone resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These changes cause suppression of 1α-hydroxylase enzyme activity, which prevents the conversion of vitamin D into the active form 1,25(OH) 2 D 3 (calcitriol). 3 Most cases of pediatric CKD in Indonesia are detected at an advanced stage, 4 including those in West Sumatra and its surroundings who seek treatment at Dr. M. Djamil Hospital, Padang, West Sumatera. In addition, due to sociocultural factors, most children wear school uniforms that cover most of their body, reducing sun exposure and leading to decreased vitamin D and increasing the risk of CKD-MBD as CKD complications.…”
mentioning
confidence: 99%